Perilaku Imitasi Fashion pada Remaja Pecinta Anime di Purwokerto - Qonita Fitriannisa Riyadie (Program Studi Ilmu Komunikasi UII, 2022)
The background of this research is the widespread development of anime culture in Indonesia which is disseminated through various media platforms, such as television and magazines. Public acceptance in Indonesia, especially teenagers, of the culture originating from Japan has an impact on their desire to imitate. These teenagers even often position themselves as big fans of the characters in anime. This is often shown in imitation of the style of dress and dress up that is usually done by their idols in the anime. On this basis, this study will reveal the effect of anime on the way anime lovers dress, as well as see what motivations lie behind the imitation pattern. This study used the descriptive qualitative method. The informants of this research are teenagers in Purwokerto. The criteria for informants are anime-loving teenagers who are in the age range of 15-24 years. The data in this study were obtained through direct in-depth interviews. The results showed that there was a restructuring of consciousness in adolescents after watching anime. Teenagers judge anime clothes as unique and interesting. They imitate the style of clothing as costumes in certain events as well as collect them. The adolescent motivation in imitation is based on the desire to get recognition from others (need for affiliation).